Mobile Applications in Agriculture: An Overview - Kambale, Parashuram; Chowhan, Vikas; Bhattad, Rakesh; S. Ragunath (Journal of Agricultural Extension Management, 2021)
Mobile or Smartphone applications, called Apps are gaining importance in agriculture. Farmer can get all solutions and information in just one touch through the Apps. The information is stored in mobile handset for easy access, for example, the details of the package of practices, pest and disease information, and scheme-related information. The majority of Indian farmers are small-scale producers. They are often unable to access the information and technological resources that could increase the yield and get better prices for their crops and products. The widespread network of mobile phones came to the rescue to tackle this problem. Most Apps are helpful only for specific information, while others are multi-informant. This paper reviews the available mobile Apps in agriculture in India meant for farmers and other stakeholders.